Seedling Diversity Considerably Changes Near Localities in Three Salinity Zones of Sundarbans Mangrove Forest, Bangladesh - ASM Helal Siddiqui; Md. Masudur Rahman; Md. Najmus Sayadat Pitol; Md. Akramul Islam; Sk Md. Mehedi Hasan (Journal of Tropical Biodiversity and Biotechnology, 2021)
The status of natural seedlings near localities in the Sundarbans Mangrove Forest was assessed through a stratified random sampling method  to observe seedling composition and diversity, importance value index, family importance value, and species evenness. A total of 63 sample plots of 3,990 m2 area were surveyed in three natural and anthropogenic influenced salinity zones of Sundarbans. A total of 16,166 seedlings of 15 species under 12 families were found. Family Euphorbiaceae showed the highest (59.59%) family relative density and Rhizophoraceae presented the highest (20%) family relative diversity Index (FRDI). The maximum family importance value (FIV) showed by Euphorbiaceae (66.26) and the maximum importance value index (IVI) of species has been observed in Excoecaria agallocha (114.74). Excoecaria agallocha showed the highest relative density (59.6%) and relative abundance (39.87%) where the highest relative frequency (15.27%) was observed by Heritiera fomes. The mean stem density and species diversity index in the whole survey area was 2701 stem ha-1 and 0.0009 correspondingly. The Shannon-Wienner's diversity index was 1.52 where the maximum Shannon-Wienner's diversity index was 2.708. The Simpson's diversity index and Dominance of Simpson index were 0.38 and 0.62 with Simpson's reciprocal index 2.632. The Species evenness index, Menhinick’s, and Margalef's indices were 0.561, 0.118, and 1.445 respectively. The Species diversity index of the three salinity zones were 0.0017, 0.0029, and 0.0035 respectively. The Shannon-Wienner's diversity index of Low Salinity Zone (LSZ), Moderate Salinity Zone (MSZ), and Strong Salinity Zone (SSZ) were 0.887, 1.369, and 1.845 correspondingly where LSZ (0.632) showed the highest Simpson's diversity index follow ed by MSZ (0.394) and SSZ (0.21). The Species evenness index for LSZ, MSZ, and SSZ were 0.346, 0.505, and 0.742 where Menhinick’s Index were 0.148, 0.210, and 0.207 respectively. The analysis showed poor diversity indices and the area was dominated by few species with few families. The status is also reduced with increasing salinity.